(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article to analyse some works psychologist and specialist in study of literature about essence concept psychotype. The auther article to systematize look to standardization psychotype. The analytical survey specialist in study of literature works to confirm problem psychotype character demand well-founded study.